Road Rage and Anger-Provoking Situations in Sulaimani City- Iraq - Karim, Hardy Kamal; Sharif, Burhan Muhammed (Sulaimani Journal for Engineering Sciences, 2023)
Driver behavior factors, including road rage factor, are often responsible for increasing traffic accidents that result in deaths, physical injuries, psychological problems, and financial losses. In order to improve traffic safety problems in our country, road rage issues related to anger-provoking situations were explored. To collect data, two questionnaire survey forms related to road rage level, traffic characteristics, and demographics of the drivers were prepared. The road rage questionnaire form included 12 questions related to popular anger-provoking situations. Six Likert scales were scored starting from 0% to 100%. Out of 600 spread forms, 463 valid forms were accepted to be analyzed. Different participants having different gender, age, education level, driving experience, vehicle type, daily travel time, vehicles’ price, traffic accidents, and the road rage history were contributed. A statistical software program (SPSS 26) was utilized to analyze the data. It was obtained that there are significant correlations among road rage-provoking anger questions and the total overall rate of the road rage. On the other hand, the results showed that male drivers are angrier than female drivers during driving. The older the drivers, the less overall road rage values were obtained. The overall road rage value decreased as the education level of the drivers raised to higher level. Driver skills had significant effects on the results of the overall road rage value of the drivers in which the drivers having 4 to 6 years of driving license were angrier than the other drivers, while drivers having driving license more than 6 years had the less feeling of anger during driving. Regarding types of vehicles, the bus, taxi, and then truck drivers had more overall road rage values than PC and SUV drivers. As the drivers traveled more distances, the obtained results of the overall road rage values became greater. The drivers who have high-price vehicles were angrier than those have low-price vehicles. The Drivers’ accident history did not significantly relate to overall road rage values. In addition, the drivers who did not have any road rage history in their real life had the smallest overall road rage values; while those drivers faced physical fighting and engaged police stations due to road rage problems had the greatest overall road rage value.
Keywords: Road rage; Drivers’ behavior; Anger-provoking